Cause of Death in Patients with Acute Coronary Syndrome. (27th December 2016) - Nishizaki, Yuji; Miyauchi, Katsumi; Okazaki, Shinya; Tamura, Hiroshi; Okai, Iwao; Ogita, Manabu; Kato, Yoshiteru; Tsuboi, Shuta; Konishi, Hirokazu; Naito, Ryo; Kurata, Takeshi; Daida, Hiroyuki
Abstract : Background: It is important to assess cause of death in patients with acute coronary syndrome (ACS) to improve the accuracy of prognosis. Methods: We investigated the cause of death in 221 patients with a first diagnosis of ACS. Results: In the short‐term outcome, the major cause of death was cardiovascular disease (35/50, 70.0%). In the long‐term outcome, non‐cardiovascular death was the major cause of death (97/171, 56.7%). The major preventable causes of death were pneumonia (13/171, 7.6%) and heart failure (19/171, 11.1%). Conclusions: The major preventable causes of death in patients with ACS are pneumonia and heart failure in the long‐term outcome.